Spaces of Memory in Cities with a Difficult History – Conflicts in Urban Narrations - Karwińska, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article discusses the controversies around memory spaces that arise as an effect of historical processes. Different groups of city dwellers and users create their own important spaces and build their vision of the city. By doing so they use urban space and history to most effectively mark their presence in them. Some parts of city may have a difficult history where a wanted and an unwanted heritage coexist. Memory in urban space can be perceived as a tool that helps to define oneself in relation to others. This memory can also be used to create the meaning of one’s own actions, choices and evaluation criteria. The author presents different examples of cities with a difficult history to discuss the thesis on the controversial character of memory spaces created by different groups.